Totalitarian state: events and questions. - SHELSHAKOVA, NATALIA NIKOLAEVNA (The journal of contemporary issues in business and government, 2021)
The article examines the problems of human life in a totalitarian state. Examples of the use of violence against adults and children are given. Describes the harsh treatment of free-thinking citizens. It is assumed that the increase in the number of diseases in children is directly related to the quality of imported products, therefore, it is recommended to check for the content of psychoactive substances and other components that negatively affect the nervous system of children. A special threat to civilians in a totalitarian state can be represented by experiments on people in order to intimidate and influence the psyche. Particular attention should be paid to sex education, namely, the satisfaction of cognitive, family needs within the framework of moral principles. It should be taken into account that when taking psychoactive substances, libido in relation to a spouse or spouse decreases (oppression of the brain centers responsible for processing sensory information), which leads to negative consequences.